Ability to Gain Control Over One’s Own Brain Activity and its Relation to Spiritual Practice: A Multimodal Imaging Study - Kober, Silvia E.; Witte, Matthias; Ninaus, Manuel; Koschutnig, Karl; Wiesen, Daniel; Zaiser, Gabriela; Neuper, Christa; Wood, Guilherme (Frontiers in Human Neuroscience, 2017)
Spiritual practice, such as prayer or meditation, is associated with focusing attention on internal states and self-awareness processes. As these cognitive control mechanisms presumably are also important for neurofeedback, we investigated whether people who pray frequently (N=20) show a higher ability of self-control over their own brain activity compared to a control group of individuals who rarely pray (N=20). All participants underwent structural magnetic resonance imaging (MRI) and one session of SMR (sensorimotor rhythm, 12-15 Hz) based neurofeedback training. Individuals who reported a high frequency of prayer showed improved neurofeedback performance compared to individuals who reported a low frequency of prayer. The individual ability to control one’s own brain activity was related to volumetric aspects of the brain. In the low frequency of prayer group, gray matter volumes in the right insula and inferior frontal gyrus were positively associated with neurofeedback performance, supporting prior findings that more general self-control networks are involved in successful neurofeedback learning. In contrast, participants who prayed regularly showed a negative association between gray matter volume in the left medial orbitofrontal cortex (Brodmann’s area 10) and neurofeedback performance. Due to their regular spiritual practice, they might have been more skillful in gating incoming information provided by the neurofeedback system and avoiding task-irrelevant thoughts.